IN VIVO ANTITUMOR ACTIVITY OF PHYTOCHEMICAL PITC-2 OBTAINED FROM TISSUE CULTURED PLANT PLUCHEA INDICA ON SARCOMA-180 SOLID TUMOR MICE MODEL - Goswami, Soumita; Debnath, Souvik; Karan, Saumen; Kumar Chatterjee, Tapan (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: PITC-2 was isolated from the methanolic root extract of tissue cultured medicinal plant Pluchea indica (L.) Less. PITC-2 is a thiophene derivative which is 2-(Prop-1-ynyl)-5(5,6-dihydroxyhexa-1,3-diynyl)-thiophene. The main objective of the study is to evaluate the in vivo antitumor activity of PITC 2 against sarcoma-180 cancer cell in Swiss albino mice. Methods: The antitumor activity was evaluated by treatment with PITC-2 at a dose of 2.5 and 5 mg/kg b.w for 21 days on sarcoma-180 mice model. Cell viability was studied using 3-(4, 5- dimethylthiazol -2-yl)-2, 5-diphenyl tetrazolium bromide assay and cell apoptosis, G1 cell cycle arrest and reduction in tumor cell proliferation were evaluated by histopathological analysis and Bcl-2, cyclic-D1, and Ki-67 protein expression through immunohistochemistry study. Results: Precisely, PITC-2 had a cytotoxic effect on various in vitro cancer cells. Significant decreases in solid tumor volume and weight along with increase lifespan also observed. The histopathological and immunohistopathological examination indicates that PITC-2 induces apoptosis, typical morphological changes and suppresses tumor cell proliferation along with G1 cell cycle arrest through the downregulation of the intratumoral expression of Bcl-2, cyclic D1, and Ki-67 and thus highlighting antiproliferative and apoptotic properties against sarcoma-180 in vivo solid tumor model. Conclusion: The present results clearly demonstrate that PITC-2 significantly inhibits sarcoma-180 cell growth in a dose-dependent manner in in vivo mice model. Besides this, the study reveals a comprehensive perception of the possible mechanism behind the antitumor activity of PITC-2 by significant changes in the morphological, hematological, biochemical parameters in sarcoma-180 cells.